Green Rating of Existing School Facilities. (November 2015) - Filippi, Marco; Sirombo, Elisa
Abstract: EU Directives promote the implementation of energy efficient measures that address to the existing building stock as a key issue to achieve relevant environmental targets. The development of methods and tools to improve the sustainability of existing facilities, instead of simple energy retrofit, could be a greater challenge. The paper discuss the ongoing development of a green audit methodology within the research project "Green School promoted in collaboration with the Province of Turin, aimed to facilitate the transformation of existing school buildings in sustainable school facilities. A multi-criteria approach that considers environmental, social and economic aspects is proposed.